Irregular Immigration in a Global Context : Drivers, Impacts, and Policy Solutions - Multan, Anastasiya (2025)
The thesis "Irregular Immigration in a Global Context: Drivers, Impacts, and Policy Solutions" explores the complex issue of irregular migration. It analyzes key drivers, including economic decline, economic inequality, and social networks, which influence individuals' decisions to migrate irregularly. To investigate these drivers in more detail, the thesis examines the correlation between the number of irregular migrants detected in the EU between 2015 and 2023 and the Fragile State Index (FSI). Additionally, the thesis studies both the positive and negative impacts of irregular migration on host countries, highlighting that while it can address labor shortages in certain sectors, it can also exacerbate social inequality and create integration challenges. The research also emphasizes the national policies and regional agreements of the case countries (the USA, the EU, and Australia), as well as the role of international organizations like the UNHCR and IOM in managing irregular migration.